PENYELESAIAN KREDIT MACET KENDARAAN BERMOTOR KARENA DEBITUR WANPRESTASI DALAM PERJANJIAN PEMBIAYAAN KONSUMEN DI PT. FEDERAL INTERNATIONAL FINANCE (FIF) KOTA BANDAR LAMPUNG - Mutia Marta Hendriani (Universitas Lampung, 2021)
There are many ways to purchase a vehicle, including a credit system. However, various problems arise in its application regarding the settlement of bad loans caused by default debtors. This study aims to analyse the efforts made by Federal International Finance Ltd. (FIF) Bandar Lampung City in resolving motor vehicle bad loans due to default debtors. This study uses empirical normative legal research methods and qualitative descriptive methods. The data is obtained from direct observations and interviews, then linked to legal regulations concerning the default problem. The results indicate that Federal International Finance Ltd. has an ideal solution to resolve bad Loans through litigation and non-litigation. Efforts to settle bad loans through non-litigation could be made by giving a subpoena to the debtor. Furthermore, the creditor could take litigation by filing a civil lawsuit against the debtor for default according to Article 1243 of the Civil Code.